Management of fatigue in children and adolescents with cancer and in paediatric recipients of haemopoietic stem-cell transplants: a clinical practice guideline. (May 2018) - Robinson, Paula D; Oberoi, Sapna; Tomlinson, Deborah; Duong, Nathan; Davis, Hailey; Cataudella, Danielle; Culos-Reed, Nicole; Gibson, Faith; Götte, Miriam; Hinds, Pamela; Nijhof, Sanne L; van der Torre, Patrick; et al.
Summary: Fatigue is a prevalent and distressing symptom in children and adolescents with cancer and in those who have undergone haemopoietic stem-cell transplantation. A multidisciplinary and multinational group of experts in paediatric oncology and fatigue, together with patient advocates, developed a clinical practice guideline for management of fatigue on the basis of systematic reviews that included six paediatric and 456 adult randomised studies. We used the Grading of Recommendations Assessment, Development and Evaluation approach to generate recommendations, and made strong recommendations, supported by evidence of moderate quality, for use of physical activity, relaxation, and mindfulness to reduce fatigue. When these approaches are unsuccessful or not feasible, cognitive or cognitive behavioural therapies may be offered (weak recommendation supported by evidence of moderate quality). Maturity and cognitive ability of individual patients will affect the feasibility of interventions. Systemic pharmacological approaches should not be routinely used to manage fatigue in children. Apart from identification of optimal approaches to implement recommended interventions in clinical practice, future research should also address knowledge gaps, including establishment of minimum age thresholds for interventions and inclusion of paediatric patients in randomised trials of fatigue management.